MANAJEMEN PENDIDIKAN KARAKTER UNTUK MENINGKATKAN RELIJIUSITAS SISWA DI MAN 2 TULUNGAGUNG DAN MA DARUL HIKMAH TAWANGSARI TULUNGAGUNG - Nuha, Muhammad Kadziqun (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
AbstractIn the era of globalization like today, community especially those who livein a development country such as Indonesia, are faced with a conditionwhich is completely modern but risky to the degradation of moral value.Characteristic education is essentially aimed at shaping the nation'stough, competitive, high morals, tolerant, worked together, patriotic spirit,developing a dynamic, oriented science and technology which are allinspired by faith and piety to God Almighty based on Pancasila.Looking at how noble these goals of education are, school, as a partywhich has a full responsibility in implementing the educational process,has to have a strong eagerness and commitment to make these goals cometrue. School has to work hard and give its full concentration to bring thesegoals into reality by maximizing all of its strengths and totallyminimizing its weaknesses. That is why, school needs to conduct acharacteristic education management to reach the national educationalgoals and its institutional goals Keywords: Characteristic Education, Characteristic Education Management, Students’ Religiosity.